Kidding rate of artificial insemination with Boer goat liquid semen during chilled preservation using coconut water-based diluent - Salim, Muhammad Ade; Ihsan, Muhammad Nur; Isnaini, Nurul; Susilawati, Trinil (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
The quality of liquid semen with coconut water as diluent could be preserved up to 3 to 4 days during cold storage at 4 - 5oC. In this research, the successful insemination rate of coconut water-based diluent Boer goat liquid semen was observed to understand the application of coconut water as semen diluent. The materials used in this research were 5 to 7 months Viridis coconut water, liquid semen from 3 years old Boer buck, 30 does for acceptor, and Tris-aminomethane added with 10% egg yolk (EY) as a control diluent. The Boer semen was collected once a week by using artificial vagina, diluted and then stored before used for insemination. The insemination was done by using intra-cervical method at position 3, started with estrous synchronization by using 2 mL PGF2α. The research was conducted as experimental method under randomized group design with two treatments, that were Tris-aminomethane + 10% EY (P0) and coconut water + 10% EY (P1). All of the treatments were repeated for 15 times and the collected data were analyzed with Pearson’s chi square with Genstat 18 program. The observed variables include non-return rate and kidding rate. The results showed that the first non-return rate of P1 were 93.33% and in P0 were 73.33%, while the second non-return rate of P1 were 93.33% and in P0 were 80%. Furthermore, the kidding rate of P1 were 40% and P0 were 66.66%. The Pearson’s chi square analysis showed that there was no effect of coconut water as semen diluent to the kidding rate. The research concludes that the usage of coconut water as semen diluent did not affect the successful insemination rate of Boer goat.